1993
DOI: 10.1007/bf00237054
|View full text |Cite
|
Sign up to set email alerts
|

The role of the conversion of IBA into IAA on root regeneration in apple: introduction of a test system

Abstract: A test system for root regeneration was developed that consists of stem slices of apple shoots (ca. 0.5 mm thick; fresh weight ca. 1 mg). Roots regenerated synchronously without intervening callus formation and without interference with compounds originating from other parts of the plant. Supply of indolebutyric acid (IBA) or indoleacetic acid (IAA) induced maximally an average of 8 or 4.5 roots per slice, respectively. After uptake of IBA, a high degree of conjugation resulted in a recovery of 2.5% as interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(37 citation statements)
references
References 14 publications
3
28
0
1
Order By: Relevance
“…With IBA, the percentage of clones that survived after transplanting to the field increased by 150%, i.e., comparing IBA (42%) with control (17%) (table II). Layers treated with auxin [21]. Our data further supported Hartmann et al that IBA is the best auxin, with a wider concentration range than NAA, and is effective in promoting rooting of a large number of plant species [15].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…With IBA, the percentage of clones that survived after transplanting to the field increased by 150%, i.e., comparing IBA (42%) with control (17%) (table II). Layers treated with auxin [21]. Our data further supported Hartmann et al that IBA is the best auxin, with a wider concentration range than NAA, and is effective in promoting rooting of a large number of plant species [15].…”
Section: Resultssupporting
confidence: 89%
“…Perhaps it would be appropriate to deduce that, in addition to vigorous and more roots being produced due to auxin application, reduction in the period of rooting gave the layers better chance of survival after transplant. We could describe the activity of auxin, especially IBA, as having increased the rate of morphogenesis of the cells at the point of incision through synergistic reaction with endogenous IAA, as opined by Vander Krieken et al [21]. Our data showed that concentrations above 3% were injurious to the layers and resulted in a low survival rate of the propagules.…”
Section: Resultssupporting
confidence: 60%
“…IBA may enhance rooting via increase of internal free IBA or many synergistically modify the action of IAA or endogenous synthesis of IAA. IBA can enhance tissue sensitivity to IAA and increase rooting (Vander Krieken et al, 1993). Markovic et al (2014) reported highest rooting percentage (96.7 %) in cornelian cherry by using terminal cuttings with current season's wood only, treated with 1% IBA (powder dip).…”
Section: Resultsmentioning
confidence: 99%
“…Peeters et al (1991) reported that NAA was taken up six times faster than IAA and Van der Krieken et al, (1993) confirmed that IBA was taken up four times faster than IAA.…”
Section: In Vitro Rootingmentioning
confidence: 96%